Studies in Linguistics and Philosophy
DOI: 10.1007/978-1-4020-4796-1_13
|View full text |Cite
|
Sign up to set email alerts
|

Information-Structural Semantics for English Intonation

Abstract: the present author, have offered different but related accounts of intonation structure in English and some other languages. These accounts share the assumption that the system of tones identified by Pierrehumbert (1980), as modified by Pierrehumbert and Beckman (1988) and Silverman et al. (1992), has as transparent and type-driven a semantics in these languages as do their words and phrases. While the semantics of intonation in English concerns information structure and propositional attitude, rather than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
2
7

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 43 publications
1
48
2
7
Order By: Relevance
“…A weak but unpredicted finding is the very small effect observed for boundary marking, where words with the lowest frequency are slightly more likely to be perceived as preceding a boundary. There is no strong basis for predicting low frequency words to be positioned at the end of a prosodic phrase, though it's possible that this weak effect in our data is related to the preference in English for topics or themes (typically given information) to be positioned at the beginning of a sentence (Steedman, 2008). …”
Section: Cue-based Prosodic Ratings (Q3)mentioning
confidence: 63%
“…A weak but unpredicted finding is the very small effect observed for boundary marking, where words with the lowest frequency are slightly more likely to be perceived as preceding a boundary. There is no strong basis for predicting low frequency words to be positioned at the end of a prosodic phrase, though it's possible that this weak effect in our data is related to the preference in English for topics or themes (typically given information) to be positioned at the beginning of a sentence (Steedman, 2008). …”
Section: Cue-based Prosodic Ratings (Q3)mentioning
confidence: 63%
“…[10]) rather than as being a reflection of topichood. In short, one could argue that it is not corrective topic or focus per se that is expressed differently, but that the difference is due to the low-level contrast feature that functions within both topic and focus and that topichood or focusing do not determine accent type in contrast to what has been suggested in the literature [13,14]. The above argument is corroborated by the fact that previous work [2] has shown that, for Greek, the tonal pattern for topic in declaratives is the same as the tonal pattern for focus in interrogatives and vice versa, suggesting that it is the boundary tone that "selects" NPA type, ultimately associating the latter to the discourse role of the former, further disassociating NPA type from topichood or focusing.…”
Section: Discussionmentioning
confidence: 92%
“…Intuitively, the intonation in (4) Rooth's (1985) alternative-based semantics for focus (Büring 1997(Büring , 2003Steedman 2008, Wagner 2008, 2012Tomioka 2010;Constant in prep.). At the heart of Rooth's interpretation system is the idea that a focused phrase generates alternatives of the same semantic type as the phrase itself.…”
Section: Background On Contrastive Topicmentioning
confidence: 99%